Shark teeth from Pirabas Formation (Lower Miocene), northeastern Amazonia, Brazil - Costa, Sue Anne Regina Ferreira; Richter, Martha; Toledo, Peter Mann de; Moraes-Santos, Heloísa Maria (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
The shark fauna (Chondrichthyes: Elasmobranchii) of Pirabas Formation is one of the most representative and diversified of the Neogene of South America. This fauna is associated with the early Miocene transgression resulting from the global sea level rise. In this paper, the composition of the Pirabas shark fauna is re-evaluated based on new fossil findings. The occurrence of the following taxa is confirmed: Carcharhinus sp.1, Carcharhinus sp.2, Carcharhinuscf. macloti, Carcharhinus priscus, Galeocerdo sp., Sphyrna cf. media, Hemipristis serra, Carcharodon subauriculatus, Isurus sp., Ginglymostoma sp., Nebrius obliquus.
Keywords: Pirabas Formation; Chondrichthyes; Neogene; Amazonia